Inclusive Education Awareness: Muslim Community Response to The Jurisprudence of Disability in Yogyakarta - Soleh, Akhmad; Muhamad, Ahmad Shamsuri; Libriyanti, Yuyun (Analisa: Journal of Social Science and Religion, 2024)
This study explores community perspectives on individuals with disabilities, recognizing consensus despite diverse viewpoints. Individuals with disabilities, whether physical or non-physical, are acknowledged to exhibit specific deficiencies while excelling in other aspects, warranting specialized attention, treatment, and facilities distinct from those serving non-disabled individuals. Our analysis, which uses qualitative field research methods, reveals a lack of public awareness of disability jurisprudence, especially in Yogyakarta. Interviews revealed a lack of awareness among the Muslim community, emphasizing the crucial role of disability Fiqh in guiding rituals and determining the validity of worship practices for individuals with disabilities. The findings underscore an information gap on the Fiqh of disability empowerment in Yogyakarta, emphasizing the need for a broader awareness campaign through various media channels. In addition, people with disabilities face significant challenges during worship, necessitating concrete collaborative efforts from the government, religious organizations, and the wider community to provide facilities and support. It is imperative to increase public understanding of disability jurisprudence and make concerted efforts to address information gaps, fostering a more inclusive worship environment for people with disabilities.